Cash Ratio, Debt to Equity Ratio, Return on Equity, Firm Size dan Net Profit Margin Terhadap Dividen Per Share Perusahaan Consumer Goods Listing BEI Perioder 2011-2014 - Saputra, Alex; Walujadi, Dedi; Amin, Akhmad Bakhtiar (Jurnal Manajemen, 2016)
From the results of hypothesis testing via t test, showed that partial. there is a positive and significant influence Cash Ratio, Debt to Equity Ratio, Return on Equity, Firm Size and Margin Net Proft against Dividends Per Share. From the results of hypothesis testing through F test showed that simultant there is a positive and significant influence Cash Ratio, Debt to Equity Ratio, Return on Equity, Firm Size and Net Proft Margin against Dividends Per Share In this case, the net profit margin as the dominant predictor of positive and significant impact on Dividend Per Share. Because, the acquisition value of the slope or regression coefficient in the net profit margin is the highest value than Slop or regression coefficient on the Cash Ratio, Debt to Equity Ratio, Return on Equity and Firm Size.